Molecular phylogenetics and biogeography of the Neocellia Series of Anopheles mosquitoes in the Oriental Region - Morgan K. (2014)
Molecular studies of population divergence and speciation across the Oriental Region are sparse, despite the region's high biodiversity and extensive Pliocene and Pleistocene environmental change. A molecular phylogenetic study of the Neocellia Series of Anopheles mosquitoes was undertaken to identify patterns of diversification across the Oriental Region and to infer the role of Pleistocene and Pliocene climatic change. A robust phylogeny was constructed using CO2 and ND5 mitochondrial genes and ITS2 and D3 nuclear ribosomal markers. Bayesian analysis of mitochondrial genes was used to date divergence events. The repeated contraction and expansion of forest habitat resulting from Pleistocene climatic fluctuations appears to have had a substantial impact on intraspecific diversification, but has not driven speciation within this group. Primarily early to mid Pliocene speciation was detected within the Annularis Group, whereas speciation within the Maculatus and Jamesii Groups occurred during the mid and late Pliocene. Both allopatric divergence driven by late Pliocene environmental changes and ecological adaptation, involving altitudinal replacement and seasonality, are likely to have influenced speciation in the Maculatus Group. © 2009 Elsevier Inc. All rights reserved.